Payton Boyles: capstone - Boyles, Payton, artist (Colorado State University. Libraries, 2024)
The artist's statement: I am a digital artist that works primarily in photoshop, my work is a blend of the whimsical and the playful. I am inspired by the playful narratives of cartoon illustration. My artistic practice is rooted in a desire to bounce off of a little humor and obscurity into every piece, creating compositions that provoke light heartedness. I experiment with exaggerated forms, muted colors, and inhuman expressions to craft scenes that not only entertain but also resonate on a personal level. My goal is to challenge and play with the mundane realities of everyday life. Through my art, I invite viewers to embrace a lighter, more playful perspective on life.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design